The motivations and needs of teachers’ training (Training and Practice : Journal of Educational Sciences, 2017)
The aim of the research is to examine the teachers’ motivation for learning and training. Research was directed towards to explore the factors that influence educators in learning, training, motivation, and to what extent the various motives influenced individuals’ self-education. Research issues include the verification of the topic whether the educator career has or has not changed the introduction of the training needs and the training product.In the light of the results of the research motivational opportunities, techniques that have been applied to learning, trainings, motivation to help educators meet the leaders of the institution are presented. In a knowledge-based society it is important for educators to learn how to support the new knowledge, the development of competences.